2021
DOI: 10.3390/cancers13236005
|View full text |Cite
|
Sign up to set email alerts
|

The MEK/ERK/miR-21 Signaling Is Critical in Osimertinib Resistance in EGFR-Mutant Non-Small Cell Lung Cancer Cells

Abstract: Background: The third-generation epidermal growth factor receptor (EGFR) inhibitor, Osimertinib, is used to treat non-small cell lung cancer (NSCLC) patients with tyrosine kinase inhibitor (TKI) resistance caused by acquired EGFR T790M mutation. However, patients eventually develop resistance against Osimertinib with mechanisms not yet fully clarified. Activated alternative survival pathways within the tumor cells and cancer-associated fibroblasts (CAFs) have been proposed to contribute to Osimertinib resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…(Wang et al, 2021) also observed that exosomal miR-25-3p induced cell proliferation and resistance to temozolomide in glioblastoma through down-regulation of FBXW7, promoting c-Myc and cyclin E expression. MiR-21-5p, also observed up-regulated in this study, was shown by (Huang et al, 2021) to negatively regulate the tumor suppressor PDCD4 and cause resistance to by Osimertinib by interfering with MEK/ERK signaling.…”
Section: Discussionsupporting
confidence: 67%
“…(Wang et al, 2021) also observed that exosomal miR-25-3p induced cell proliferation and resistance to temozolomide in glioblastoma through down-regulation of FBXW7, promoting c-Myc and cyclin E expression. MiR-21-5p, also observed up-regulated in this study, was shown by (Huang et al, 2021) to negatively regulate the tumor suppressor PDCD4 and cause resistance to by Osimertinib by interfering with MEK/ERK signaling.…”
Section: Discussionsupporting
confidence: 67%
“… 203 CAFs in osimertinib-resistant NSCLC cell lines release higher IL-6, IL-8, and HGF and express more CAF markers like α-smooth muscle agonists-α (α-SMA), fibroblast activation protein (FAP), and PDGFR. 204 The same scenario can be seen in patients with metastatic RCC. 205 HGF can bind to MET on cancer cells to activate MEK/ERK signaling pathway.…”
Section: Mechanisms Of Tki Resistancementioning
confidence: 76%
“…Many miRNAs have been implicated in tumorigenesis, functioning as either oncogenes or tumour suppressors. miR-21 affects the biological status, such as invasion, of NSCLC cells through aberrant EGFR signalling [20]. Some miRNA alterations and targeting effects have been found in NSCLC.…”
Section: Discussionmentioning
confidence: 99%